Sistema de información contable y toma de decisiones en la Municipalidad Provincial de Requena 2024 - Pacaya Flores, Brandy Brayan (2024)
The main objective of the research carried out was to determine the relationship between the accounting information system and decision-making in the Provincial Municipality of Requena 2024. This is an applied study, descriptive and correlational, in which 108 workers participated who answered a Likert scale questionnaire. As a result, it was determined that the accounting information system in the municipality presents a regular level (29%), due to the fact that sometimes a systematic record of financial events is not carried out following current regulations. In terms of decision-making, it is also considered a regular level (28%), as a thorough analysis is often carried out considering various alternatives when faced with a problem. Finally, there is a significant positive relationship (rho=0.848; sig.=0.000) between the accounting information system and decision-making in the Provincial Municipality of Requena 2024.